The Effect of Self-Directed Learning Strategy on Students Reading Comprehension at SMP Swasta Pembda 2 Gunungsitoli - Mendrofa, Tri Hartati; Harefa, Afore Tahir; Harefa, Trisman; Telaumbanua, Kristof Martin Efori (Journal of English Language and Education, 2025)
This study aims to evaluate the effect of self-directed learning (SDL) strategies on students' reading comprehension at PEMBDA 2 Gunungsitoli Private Junior High School. The background of this study shows that students experience difficulties in understanding reading texts, which has a negative impact on their academic development. The research method used was quasi-experimental with a pretest-posttest design involving two groups: an experimental group using the SDL strategy and a control group using conventional methods. The results showed a significant increase in students' reading comprehension skills in the experimental group compared to the control group. The average pretest score of the experimental group was 43.47 and increased to 89.47 on the posttest, while the control group only increased from 36.27 to 48.13. The t-test showed a significance value (p 0.05), indicating the effectiveness of the SDL strategy in improving reading comprehension. In addition, the N-Gain value for the experimental group was 0.814 (high category), while the control group was only 0.185 (low category). The conclusion of this study is that the application of the SDL strategy significantly improves students' reading comprehension skills, creating a more independent, enjoyable, and meaningful learning experience. This study recommends the use of the SDL strategy in English teaching at the junior high school level as an effective method for improving student learning outcomes.